The Effect of Hierarchy on Moral Silence in Healthcare: What Can the Holocaust Teach Us? - Fernandes, Ashley K.; Ecret, DiAnn (Conatus - Journal of Philosophy, 2019)
Physicians, nurses, and healthcare professional students openly (and in many cases, eagerly) participated in the medical atrocities of the Shoah. In this paper, a physician-bioethicist and nurse-bioethicist examine the role of hierarchical power imbalances in medical education, which often occur because trainees are instructed ‘to do so’ by their superiors during medical education and clinical care. We will first examine the nature of medical and nursing education under National Socialism: were there cultural, educational, moral and legal pressures which entrenched professional hierarchies and thereby commanded obedience in the face of an ever-diminishing individual and collective conscience? We will then outline relevant parallel features in modern medical education, including the effects of hierarchy in shaping ethical decision making and conscience formation. We then propose several solutions for the prevention of the negative effects of hierarchical power imbalances in medical education: (1) universal Holocaust education in medical and nursing schools; (2) formative and experiential ethics instruction, which teaches students to ‘speak up’ when ethical issues arise; (3) acceptance of, and adherence to, a personalistic philosophical anthropology in healthcare; (4) support for rigorous conscience protection laws for minority ethical views that respect the role of integrity without compromising patient care.